Reduced-reference video quality metric using spatio-temporal activity information - Abdul Rahman, Farah Diyana; Ibrahim, Ahmad Imran; Agrafiotis, Dimitris (Institute of Advanced Engineering and Science (IAES), 2018)
Monitoring and maintaining acceptable Quality of Experience is of great importance to video service providers. Perceived visual quality of transmitted video via wireless networks can be degraded by transmission errors. This paper presents a reduced-reference video quality metric of very low complexity and overhead that makes use of frame based spatial (SI) and temporal (TI) activity levels to monitor the effect of channel errors on video transmitted over error prone networks. The performance of the metric is evaluated relative to that of a number of full and reduced reference metrics. The proposed metric outperforms some of the most popular full reference metrics whilst requiring very little overhead.